Clinical outcome of transthoracic esophagectomy with thoracic duct resection: Number of dissected lymph node and distribution of lymph node metastasis around the thoracic duct. Issue 24 (June 2016) - Matsuda, Satoru; Takeuchi, Hiroya; Kawakubo, Hirofumi; Shimada, Ayako; Fukuda, Kazumasa; Nakamura, Rieko; Takahashi, Tsunehiro; Wada, Norihito; Kameyama, Kaori; Kitagawa, Yuko
Abstract : Abstract: The number of dissected lymph nodes (LNs), surgical outcomes, and postoperative recurrence-free survival (RFS) were compared between thoracic duct (TD)-preserved and TD-resected groups. The distribution of metastasis in LNs around TD (TDLN) was reviewed. Transthoracic esophagectomy (TTE) with TD resection for esophageal cancer patients has been one of the standard procedures. Because the adipose tissue surrounding the TD contains LNs, TD resection might be necessary for radical LN dissection. However, few studies have investigated the oncological outcome of TTE with TD resection. Two hundred fifty-six consecutive patients who underwent TTE between 2004 and 2015 were retrospectively reviewed and classified into TD-preserved or TD-resected groups. The number of dissected LNs for each LN station and surgical outcomes were compared. RFS was analyzed in 155 patients who underwent TTE before December 2012. Since 2013, the TDLN number was prospectively examined, independent of the regional LNs (n = 72). Of these, the TDLN number for each location (TDLN-Ut/Mt/Lt) was investigated and the correlation between TDLN metastasis and clinicopathological factors was analyzed. The TD was preserved in 89 patients and resected in 167 patients. Patients with TD resection showed significant advanced stage. There was no significant difference in the incidence of postoperative complications, including pneumonia, anastomotic leakage, and chylothorax. The number of dissected mediastinal LNs was significantly increased in the TD-resected group. The 5-year RFS rate of cStage I patients was 67.3% in the TD-preserved group against 90.3% in the TD-resected group, showing a tendency towards RFS extension that did not quite reach statistical significance ( P = 0.055). The mean TDLN-Ut/Mt/Lt numbers were 0.89/0.56/0.44, respectively. Eight of 72 (11%) patients displayed TDLN metastasis. Metastatic TDLNs were observed on the same or cranial level of the primary lesion in 7 of 8 patients. Transthoracic esophagectomy with TD resection could increase the number of dissected mediastinal LNs without increase of postoperative complication. TDLN metastasis was observed in patients with advanced disease. A prospective trial, investigating the survival between TD-preserved and TD-resected groups, should be conducted to clarify if TD should be resected in TTE.